The Impact of a Pandemic on the Provision of Diabetic Foot Care. Then, Now and the Future - Roslyn Miller MB ChB, FRCS(Ed), FRCS(Tr&Oth) (Foot & Ankle Orthopaedics, 2022)
Category: Diabetes Introduction/Purpose: 2020-2022 saw the COVID-19 coronavirus pandemic. Stratification of access to theatres based on urgency resulted in many diabetic patients 'falling through the crack'. Diabetic patients with foot disease, who presented acutely and/or with sepsis were often managed by the vascular team, who often deemed that there was no salvage option available. However, patients who had recurrent ulceration but were systemically well were unable to access the theatre and clinical skills required to address the mechanical deformity that was responsible for the recurrence of the ulcer. Methods: Scotland National Database for all diabetic foot disease collates information for all new diabetic foot ulcers. The system is designed to collate data pertaining to the control of the patients' diabetes, peripheral vascular disease and smoking. It is less robust had assessing orthopaedic and biomechanical abnormalities which would benefit from surgical intervention. A collaborative approach with the diabetologists, diabetic podiatrists and orthotics, orthopaedic and vascular surgeons across Scotland has anecdotally recorded a significant reduction in services for this group of patients. Community podiatry services were redeployed during the pandemic. Access to hospital clinics and theatre utilisation was stopped for periods of time. The very first weeks had patients staying at home with loved ones and as a result, active ulcers decreased due to off-loading and patients taking care of themselves. Recovery however is painfully slow, with disjointed services. It is however an opportunity to reshape a national diabetic foot service. Results: Initial review with all the major stakeholders anecdotally has reported significant increases in diabetic foot disease during the two years of the pandemic. The lack of access to elective orthopaedic procedures has meant that patients are now presenting very late. Often the only surgical option available to save life or limb is amputation. However new ways of working have brought some benefits to patients. Virtual and remote communication has facilitated a reduction in the number of hospital visits. However, lack of coordination means that many of these patients are suboptimally managed pre and peri-operatively. Clinical competencies are very varied across the country, and there has been no face-to-face training. This is however a perfect opportunity to re-think the delivery of service and allocation of training and vital resources across the country. Conclusion: A complete review of the national picture of delivery of services for patients with diabetic foot disease allows identification of patients' needs. The allocation of resources and training needs for both surgeons and Allied Health Professionals will be identified and addressed. The main focus of the review remains the reduction in amputation rates, with an associated reduction in mortality for this group of patients.Once pathways have been reassessed, escalation should become more robust. The review will also identify major training needs.